2008
DOI: 10.1111/j.1572-0241.2007.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Evaluation of the Efficacy and Safety of Endoscopic Ultrasound-Guided Direct Ganglia Neurolysis and Block

Abstract: Initial experience suggests that EUS-guided direct celiac ganglion block or neurolysis is safe. Alcohol injection into ganglia appears to be effective in both cancer and chronic pancreatitis. Prospective trials are needed to confirm the efficacy of this new approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
138
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(148 citation statements)
references
References 10 publications
3
138
0
7
Order By: Relevance
“…Successful identification of celiac ganglia during EUS occurred in 81% of patients, with more ganglia identified with linear-array EUS. 108 Levy et al 109 reported 94% complete or partial pain relief in 18 patients with unresectable pancreatic cancer undergoing CGN. Following these promising results, a recent study randomized 68 patients with upper GI cancer pain to undergo either EUS-CPN or EUS-CGN.…”
Section: Eus-guided Anastomosismentioning
confidence: 99%
See 1 more Smart Citation
“…Successful identification of celiac ganglia during EUS occurred in 81% of patients, with more ganglia identified with linear-array EUS. 108 Levy et al 109 reported 94% complete or partial pain relief in 18 patients with unresectable pancreatic cancer undergoing CGN. Following these promising results, a recent study randomized 68 patients with upper GI cancer pain to undergo either EUS-CPN or EUS-CGN.…”
Section: Eus-guided Anastomosismentioning
confidence: 99%
“…110 Complications from CGN in both studies were minimal and similar to those observed with CPN, including but not limited to diarrhea, hypotension, bleeding at puncture site, and abdominal pain. 3,4,6,109,110 Discussion EUS with FNA remains an exceedingly accurate method in diagnosing and staging pancreatic cancer. However, this accuracy is limited in certain cases, such as chronic pancreatitis.…”
Section: Eus-guided Anastomosismentioning
confidence: 99%
“…Alcohol injection into ganglia appeared to be effective in both cancer and chronic pancreatitis. 49 Garcia et al in 2009 performed a percutaneous CPN in a 68-yearold male patient using the anterior transgastric route guided by colour Doppler ultrasonography (CDU). Magnetic resonant image (MRI) revealed a large solid mass in the head of the pancreas invading the coeliac trunk and superior mesenteric vessels with diffuse dilatation of the main pancreatic duct.…”
Section: Ultrasound Guidancementioning
confidence: 99%
“…Moreover, celiac ganglia visualization by EUS in approximately 80 % of cases [9 -12] allows direct injection [13].…”
mentioning
confidence: 99%